Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1007/s00392-008-0705-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a novel drug-eluted balloon coated with Genistein before stent implantation in porcine coronary arteries

Abstract: This is an author version of the contribution published on: Questa è la versione dell'autore dell'opera: [Effect of a novel drug-eluted balloon coated with genistein before stent implantation in porcine coronary arteries.Sheiban I, Anselmino M, Moretti C, Biondi-Zoccai G, Galloni M, Vignolini C, Mattoni M, Sciuto F, Omedè P, Trevi GP. Clin Res Cardiol. 2008 Dec;97(12):891-8. doi: 10.1007/s00392-008-0705-2.] The definitive version is available at: La versione definitiva è disponibile alla URL: [http://link… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Other agents, such as the naturally occurring MAPK inhibitor genistein and Ca 2+ activated K + channel inhibitor, have been tested for use as a coating on DEBs. In 2008, Sheiban et al reported that although the application of a genistein-coated angioplasty balloon prior to bare-metal stenting in a porcine model of coronary stenosis resulted in significant reduction of peri-stent mononucleocyte count at 4 weeks, this did not translate into reduced neointimal hyperplasia at 6-8 weeks [41]. Taxanes such as paclitaxel have high lipophilicity and bind tightly to various cell constituents [42], resulting in effective local retention at the site of delivery [43].…”
Section: Choice Of Drugmentioning
confidence: 98%
“…Other agents, such as the naturally occurring MAPK inhibitor genistein and Ca 2+ activated K + channel inhibitor, have been tested for use as a coating on DEBs. In 2008, Sheiban et al reported that although the application of a genistein-coated angioplasty balloon prior to bare-metal stenting in a porcine model of coronary stenosis resulted in significant reduction of peri-stent mononucleocyte count at 4 weeks, this did not translate into reduced neointimal hyperplasia at 6-8 weeks [41]. Taxanes such as paclitaxel have high lipophilicity and bind tightly to various cell constituents [42], resulting in effective local retention at the site of delivery [43].…”
Section: Choice Of Drugmentioning
confidence: 98%
“…The Sparrow stent (Biosensors, Singapore, Singapore) is ideally posed to become a useful adjunct to the interventionist's armamentarium aiming to treat distal and tortuous lesions [27], whereas bioabsorbable endoprostheses (Absorb, Abbott Vascular) appear as very promising alternatives to standard metallic stents when permanency of the metallic platform is called into question [26]. Finally, drug-eluting balloons might become a routine means to revascularize patients with coronary artery disease as they may represent a suitable middle man between standard balloons and drug-eluting stents [28,29].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Sheiban et al 28 tested the efficacy of a genistein-coated balloon (anti-inflammatory falconoid, 0.7 g/mm 2 ) in a porcine coronary artery stent model. They reported that at 4 weeks, peri-stent inflammatory cell count (mononucleocytes) was significantly less in vessels treated with genistein-coated balloons compared with those treated with noncoated balloons (39Ϯ32 versus 96Ϯ29 mm 2 , Pϭ0.019).…”
Section: Nonpaclitaxel Deb Preclinical Studiesmentioning
confidence: 99%